Object Tracking Dengan Menggunakan Color Filtering HSV Pada Robot World Cup - Kharis Sugiarto; Andhika Giyantara; Retno Debbi Yulisya (Prodi Ilmu Komputer Universitas Bumigora, 2022)
Robot World Cup (RoboCup) is a federation founded in 1993 to support researchers in soccer robot research. The purpose of the RoboCup is to push the latest developments or advance the technological level of society in all fields. In this research, the problem is how RoboCup can do object tracking. In recognizing objects around the robot requires an image analysis process that involves visual perception. Image processing is an image processing and analysis process that involves visual perception, the characteristics of the image process in the form of input data and output information in the form of images. This process is a way for robots to see objects around them and then assisted by computer vision to make decisions. In this research object tracking with HSV color filtering on the world cup robot is used to find objects in front of the robot with the front camera. This research for front vision robot uses HSV color filtering using various test values ​​to determine the thresholding value and the results show that the ball can be identified up to a distance of 1000 cm with a minimum illumination of 0 lux. The percentage of the success rate of the camera detecting the HSV color filtering reaches 100%.